Haters on the Internet – background, evolution and legal responsibility - Jabłońska, Marta Regina (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The main aim is a review of publications in the area of electronic aggression, especially concerning aggressors legal responsibility. To reach this goal an analysis of various papers (in Polish and English) was taken. The papers were selected due to authors’ output and contribution in area of electronic aggression. In the next step, Polish legal acts were investigated. In effect, it was stated that level of electronic aggression is growing instantly and requires further research. Also Polish law – despite some solutions already taken – demands additional improvements.